A sombra da pobreza na cidade do sol: O ordenamento dos retirantes em Fortaleza na segunda metade do século XIX - Garcia, Ana Karine Martins (2006)
This work examines documents and actions in order to comprehend the project of modernization introduced in Fortaleza at the end of XIX Century, and especially how the presence of flagellants during the drought period (1877-1880) modified the urban space and the social structure of the city. The study also analyses the construction of urban equipments in Fortaleza from 1870 on, the imaginary about the flagellants, the refugee camps and the attempts of hygienic control